Effect of acute interset foot cooling on lower limb strength training workout - Yan Cai, Z.; Yi Wang, W.; Huang, Y. M.; Wu, C. M. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The authors investigated the effect of foot cooling (FC) between sets in a leg press pyramid workout with resistance-trained participants.